Modelling clearance sales store loyalty behaviour of Indian shoppers. (4th January 2010) - Hemalatha, M.; Sivakumar, V.J.
This study seeks to investigate the influence of store attributes on clearance sales store loyalty. The study examines the influence of different store attributes such as merchandise with gifts, retail operation, retail services, discount, salesman service, promotion, retail facilities and store atmosphere on store loyalty. A total of 664 shoppers were surveyed during Aadi clearance sales in three different Indian cities. We have constructed a multiple regression model on store loyalty behaviour of clearance sales. Our store loyalty model confirms that merchandise with gifts, retail operation and discounts has the greatest impact on the clearance sales store loyalty. The findings from the study proved that higher the level of merchandise with gifts, retail operation, retail services, discount, salesman service, promotion, retail facilities and store atmosphere will lead to higher store loyalty during clearance sales event.